Cybernetic and economic aspects of reducing the risks of cloud storages in the structure of information systems - Lubenets, S.; Shelestova, A.; Pomortseva, O.; Hubin, V. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2026)
The article identifies key problematic aspects of the risks associated with the use of cloud data storage by organizations within the structure of their own corporate information systems, combining issues of technical security (cyber aspects), as well as financial feasibility and costs of cyber storage (economic aspects). The most important problematic aspects include: difficulties in designing a secure cloud storage; economic and financial aspects of managing costs of cloud services; insufficient level of proficiency in the necessary skills and / or resources for the proper design, implementation, management and maintenance of a cloud environment. To identify possible areas for mitigating the risks of cloud storage, the basic and extended principles of the "zero trust" concept are studied. Issues of ensuring the integrity and confidentiality of data in cloud storage of information systems are considered. The problem of durability as the ability of a cloud storage system to reliably protect data from loss or damage over a long period of time is studied. The essence of data sovereignty, the importance of the location of cloud storage, and the key role of their performance in minimizing the downtime of a corporate information system and ensuring data fault tolerance and business continuity are determined. The article examines the economic factors that contribute to forecasting cloud resource costs and determining the total cost of ownership for cloud storage. It also highlights the importance of ensuring compatibility between an organization's cloud storage system and previously implemented information security solutions. Key requirements for cloud storage services, resources, and solutions are formulated to mitigate risks and ensure the radical resilience of information system data. Potential areas and prospects for further research on this topic, related to the use of artificial intelligence systems, are identified.